Full paleostress tensor reconstruction using quartz veins of Panasqueira Mine, central Portugal, part II: Final results. (September 2022) - Pascal, Christophe; Jaques, Luís; Yamaji, Atsushi
Abstract: We propose a novel method to reconstruct the six parameters of the paleostress tensor. The method involves three major steps: (1) measurement and inversion of vein attitudes to determine the reduced paleostress tensor, (2) determination of pore pressures using fluid inclusion (FI) isochores and mineral geothermometry, (3) final adjustment of the Mohr circle and estimation of stress magnitudes using geomechanical constraints from the literature. Owing to its outstanding 3D exposures, we selected Panasqueira Mine, central Portugal, as natural laboratory to develop and test our approach. We measured 684 quartz veins, ∼800 FIs in quartz and the geochemical composition of 10 arsenopyrite samples. The inversion of the veins resulted in a reverse stress regime with σ1 trending ∼ NW-SE, Φ = 0.6 and a driving stress ratio of R' = 0.19. We estimated a lithostatic pressure of 270 MPa (min. 230 MPa and max. 300 MPa) during the major mineralisation stage of the veins of Panasqueira (i.e. MOSS-MSS stage). Finally, the adjustment of the Mohr circle resulted in differential stresses too low to trigger shear failure and in the range from 45 to 89 MPa, and pore pressures exceeding lithostatic pressure by 8.5–17 MPa to open the discontinuities during MOSS-MSS mineralisations. Highlights: Paleostress inversion methods are traditionally unable to reconstruct the full set of parameters defining the stress tensor. We propose a novel methodology for full determination of paleostress tensors. The method relies on inversion of veins, microthermometric analysis of fluid inclusions and geochemical analyses. Stress magnitudes are finally determined by adjustment of the Mohr circle.